Arabidopsis thaliana mutants lacking cpFtsY or cpSRP54 exhibit different defects in photosystem II repair - Walter, Björn; Pieta, Thomas; Schünemann, Danja (Frontiers in Plant Science, 2015)
Photosystem II (PS II) is a multi subunit protein complex embedded in the thylakoid membrane of cyanobacteria and chloroplasts. As the PS II reaction center protein D1 is prone to a light induced damage that inhibits PS II function especially at elevated light intensities, a highly ordered repair process including synthesis, targeting and insertion of D1 has evolved. To elucidate the function of the chloroplast signal recognition particle subunits, cpSRP43 and cpSRP54, and the cpSRP-receptor cpFtsY in D1 biogenesis we investigated the efficiency of the PS II repair cycle in the corresponding mutants of Arabidopsis thaliana. Immunological analyses, PAM measurements and in vivo labeling experiments demonstrate an impaired replacement of damaged D1 in the cpftsy mutant, while the chaos and the ffc mutant lacking cpSRP43 and cpSRP54, respectively, were not or hardly affected. The defect in cpftsy was neither caused by an impaired psbA transcript accumulation, D1 translation initiation nor by an enhanced D1 degradation. Further experiments revealed a decreased amount of salt stable, thylakoid membrane-associated translating ribosomes in the cpftsy mutant, while the amount of membrane-associated translating ribosomes is unaltered in the chaos and the ffc mutants. Therefore, our data indicate that the lack of cpFtsY leads to an inefficient PS II repair cycle caused by an impaired binding of translating ribosomes to the thylakoid membrane.